Analisis Sistem Informasi Manajemen Pada Bardi Smarthome - Fachry Hadiansyah; Ageng Saepudin Kanda S (Pusat Riset dan Inovasi Nasional, 2024)
Bardi Smarthome is one of the Smarthome product providers active in Indonesia. With the aim of marketing Smarthome products at affordable prices, Bardi Smarthome can be easily found on Indonesian online shop platforms. Not only does it sell Smarthome products at affordable prices, quality is also a concern for Bardi Smarthome. Innovation continues to occur, as well as efforts to develop Smarthome Bardi products to further help consumers' daily activities at home. Information systems used to make decisions, coordinate operations, control processes, analyze data, and visualize information in an organization are known as management information systems (MIS). This planning system is a component of a business's internal controls and includes management's use of personnel, documents, technology, and procedures to address business problems such as the cost of goods or services. The aim of this research is to find out whether the installation of the Bardi Smarthome information management system is functioning to its best capacity and how much influence it has on the way the company's operations are run. This research uses qualitative methodology and methods to collect data from the literature, including data collection, review, and analysis.